Parameters estimation of LFM signal based on Gaussian-weighted fractional Fourier transform - Peng WANG; Tian-shuang QIU; Jing-chun LI; Hai-feng TAN (Tongxin xuebao)
To overcome the performance degradation of conventiona methods in low duty ratio condition, a novel me-thod of parameters estimation for LFM signal based on the Gaussian-weighted fractional Fourier transform (GFRFT) was proposed. Firstly, the GFRFT definition was given and the LFM signal GFRFT with finite duration was derived. Secondly, the statistical characteristics of the GFRFT for the LFM signal under the Gaussian white noise were studied, and a closed mathematical expression of output signal-to-noise ratio was derived. Finally, simulation experiments are conducted, and the applicable condition of the GFRFT is also discussed, which demonstrates that the proposed method can effectively improve parameters estimation performance, especially in the low duty ratio condition.